Antihypertensive effect of Piper sarmentosum in L-NAME-induced hypertensive rats - Nik Aloesnisa Nik Mohd Alwi,; Zaiton Zakaria,; Aminuddin Abdul Hamid Karim,; Nor Anita Megat Mohd Nordin,; Azizah Ugusman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Hypertension is one of the risk factors for cardiovascular diseases and has been associated with about 13% of global deaths worldwide. Oxidative stress and reduced nitric oxide (NO) bioavailability contribute to the development of endothelial dysfunction and subsequently hypertension. Nɷ-nitro-L-arginine methyl ester hydrochloride (L-NAME) inhibits NO synthesis; leading to hypertension. Piper sarmentosum (PS) is an herb with antioxidant, antiatherosclerosis and antiinflammation properties. PS also stimulated NO production by endothelial cells. The aim of this study was to determine the effects of aqueous extract of Piper sarmentosum (AEPS) on blood pressure, oxidative stress and the level of nitric oxide in L-NAME-induced hypertensive rats. Hypertension was induced by oral administration of L-NAME (100 mg/L) in drinking water for four weeks. The rats were concurrently treated with AEPS by oral gavage in serial doses (125, 250 and 500 mg/kg/day). Blood pressure was measured using non-invasive tail-cuff method at baseline and fortnightly thereafter. Serum level of NO and an oxidative stress marker, malondialdehyde (MDA) were measured at baseline and at the end of treatment. The results showed that treatment with three different doses of AEPS successfully reduced systolic blood pressure (p<0.001), diastolic blood pressure (p<0.05) and mean arterial pressure (p<0.05) in L-NAME-induced hypertensive rats. Treatment with AEPS also reduced MDA level (p<0.001) and increased serum NO (p<0.001) in L-NAME-induced hypertensive rats. The findings showed that AEPS decreased blood pressure by protecting against oxidative stress and increasing NO in L-NAME-induced hypertensive rats.